Frailty and Short-Term Outcomes in Patients With Hip Fracture. (September 2015) - Kistler, Elizabeth A.; Nicholas, Joseph A.; Kates, Stephen L.; Friedman, Susan M.
Objectives: To assess the prevalence of frailty and its ability to predict short-term outcomes in older patients with hip fracture. Design: Prospective cohort study. Setting: University-affiliated community hospital. Participants: Thirty-five patients aged ≥65 treated with hip fracture. Measurements: Frailty was assessed using the 5 criteria of the Fried Frailty Index, modified for a post-fracture population. Cognitive impairment was assessed with the Montreal Cognitive Assessment (MoCA). The primary outcome was overall hospital complication rate. Secondary outcomes were length of stay (LOS) and specific complications. Differences between the frail and the non-frail were identified using chi-square analysis and analysis of variance (ANOVA) for categorical and continuous variables, respectively. Results: Eighteen (51%) participants were frail. Seventeen (49%) had ≥1 hospital complication. Twelve (67%) frail patients versus 5 (29%) non-frail patients had a complication ( P = .028). Mean LOS was longer in patients with frailty (7.3 ± 5.9 vs 4.1 ± 1.2 days, P = .038). Most were frail for the weakness criterion (94%), and few were frail for the physical activity criterion (9%). Excluding these criteria, we developed a 3-criteria frailty index (shrinking, exhaustion, and slowness) that identified an increased risk of complications (64.7% vs 33.3%, P = .061) and LOS (7.4 ± 6.1 vs 4.2 ± 1.3 days, P = .040) in participants with frailty. Among non-frail participants with a high MoCA score of ≥20 (n = 12), 2 (17%) had complications compared to 10 (71%) frail participants with a low MoCA score (n = 14). Conclusion: Frailty is common in older patients with hip fracture and associated with increased LOS and postoperative complications. A low MoCA score, a hypothesized marker of more advanced cognitive frailty, may further increase risk. Frailty assessment has a role in prognostic discussion and care planning. The 3-criteria frailty index is an easily used tool with potential application in clinical practice.